Consumer perceptions of B corporations, purpose-driven brands and cause-related marketing campaigns: Knowledge, acceptance and appreciation at the time of purchase (Journal of Business, Universidad del Pacífico (Lima, Peru), 2020)
For the Argentine case, studies that identify increasing implementation of three major CSR triple-impact strategies—B corporations, purpose-driven brands and marketing, and cause-related marketing—focus predominantly on supply.The present study seeks to identify consumer perceptions of these three triple-impact strategies in terms of recognition, knowledge, appreciation, and prioritization at the time of the purchase in the Argentine market.A quantitative investigation was carried out, based on a nationwide panel of 400 citizens. The results show that a majority of participants do not recognize the concepts of purpose-driven brands or the concept of B corporations. Many express difficulties in identifying such initiatives due to disinterest, ignorance, and/or lack of availability/exposure. In addition, there were non-significant differences in terms of generations, socioeconomic level, and sex. On the other hand, almost half of the panel has some familiarity with cause-related marketing campaigns, given the association with NGOs to which participating companies may donate or fund-raise. The results, particularly the limited overall recognition of these concepts, has management implications in a context of recession and spending restrictions.Video-abstract: https://youtu.be/tthIr8MSSj4
Keywords: Purpose-driven marketing; B corporations; cause-related marketing; knowledge; consumer value